Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0257977
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors Krüppel-like factor 4 and paired box 5 regulate the expression of the Grainyhead-like genes

Abstract: Genes from the Grainyhead-like (GRHL) family code for transcription factors necessary for the development and maintenance of various epithelia. These genes are also very important in the development of many types of cancer. However, little is known about the regulation of expression of GRHL genes. Previously, there were no systematic analyses of the promoters of GRHL genes or transcription factors that bind to these promoters. Here we report that the Krüppel-like factor 4 (KLF4) and the paired box 5 factor (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…33 Interestingly, TP63 ablation negatively affects DSG1 expression. 34 Furthermore, although we showed that KLF4 directly regulates DSG1, KLF4 loss-of function variants may also affect DSG1 expression indirectly because KLF4 was shown to transactivate the GRHL1 gene that encodes GRHL1, 35 and GRHL1 null mice have reduced DSG1 expression and develop PPK. 36 The mild phenotype displayed by patients harboring pathogenic KLF4 variants, a nonpainful form of PPK, contrasts with the multifaceted role of KLF4, 20 which has been shown in various mouse models to be critical for the development of a wide range of tissues, including epidermis, cornea, and gut epithelia.…”
Section: Discussionmentioning
confidence: 79%
“…33 Interestingly, TP63 ablation negatively affects DSG1 expression. 34 Furthermore, although we showed that KLF4 directly regulates DSG1, KLF4 loss-of function variants may also affect DSG1 expression indirectly because KLF4 was shown to transactivate the GRHL1 gene that encodes GRHL1, 35 and GRHL1 null mice have reduced DSG1 expression and develop PPK. 36 The mild phenotype displayed by patients harboring pathogenic KLF4 variants, a nonpainful form of PPK, contrasts with the multifaceted role of KLF4, 20 which has been shown in various mouse models to be critical for the development of a wide range of tissues, including epidermis, cornea, and gut epithelia.…”
Section: Discussionmentioning
confidence: 79%